Asymmetric Composite Nanoparticles with Anisotropic Surface Functionalities. (1st December 2008) - Wang, Yilong; Xu, Hong; Qiang, Weili; Gu, Hongchen; Shi, Donglu
Abstract : Asymmetric inorganic/organic composite nanoparticles with anisotropic surface functionalities represent a new approach for creating smart materials, requiring the selective introduction of chemical groups to dual components of composite, respectively. Here, we report the synthesis of snowman-like asymmetric silica/polystyrene heterostructure with anisotropic functionalities via a chemical method, creating nanostructure possibly offering two-sided biologic accessibility through the chemical groups. Carboxyl group was introduced to polystyrene component of the snowman-like composites by miniemulsion polymerization of monomer on local surface of silica particles. Moreover, amino group was then grafted to remained silica surface through facile surface modification of the composite nanoparticles. The asymmetric shape of these composites was confirmed by TEM characterization. Moreover, characteristics of anisotropic surface functionalities were indicated by Zeta potential measurement and confocal laser microscopy after being labeled with fluorescent dyes. This structure could find potential use as carriers for biological applications.